Characterization of a Temporal Profile of Biomarkers as an Index for Ischemic Stroke Onset Definition - Da Silva-Candal, Andrés (J Clin Med, 2021)
Background and purpose: Stroke is a dynamic process in terms of molecular mechanisms, with prominent glutamate-mediated excitotoxicity at the onset of symptoms followed by IL-6-mediated inflammation. Our aim was to study a serum glutamate/IL-6 ratio as an index for stroke onset definition. Methods: A total of 4408 ischemic stroke patients were recruited and then subdivided into four quartiles according to latency time in minutes (0–121, 121–185, 185–277 and >277). Latency time is defined as the time between stroke onset and treatment at the neurological unit. The primary endpoint of the study was the association of early latency times with different clinical aspects and serum markers. Serum glutamate and interleukin-6 (IL-6) levels at admission were selected as the main markers for excitotoxicity and inflammation, respectively. Results: Glutamate serum levels were significantly higher in the earlier latency time compared with the higher latency times (p < 0.0001). IL-6 levels were lower in early latency times (p < 0.0001). Patients with a glutamate/IL-6 index on admission of >5 were associated with a latency time of <121 min from the onset of symptoms with a sensitivity of 88% and a specificity of 80%. Conclusions: The glutamate/IL-6 index allows the development of a ratio for an easy, non-invasive early identification of the onset of ischemic stroke symptoms, thus offering a new tool for selecting early stroke patient candidates for reperfusion therapies.